2019
DOI: 10.3390/ijerph16030405
|View full text |Cite
|
Sign up to set email alerts
|

The National After-School Athletics Program Participation as a Tool to Reduce the Risk of Obesity in Adolescents after One Year of Intervention: A Nationwide Study

Abstract: Regular exercise during school hours is encouraged; however many children and adolescents fail to meet the recommendations during this time. Extracurricular activities may be a more appealing way for youth to achieve guidelines, and it is recommended that they attend two sessions each week. The aim of the study was to assess the influence of participation in a national physical activity program accompanied by nutritional education for trainers on the risk of obesity and body composition in a nationwide sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 54 publications
1
8
0
1
Order By: Relevance
“…The association between eating behaviors of mothers and their children that was observed in the conducted study is confirmed by the results of another Polish study, as a similar strong association between eating behaviors of mothers and their adolescent daughters was observed [37], and it also contributed to similar excessive body mass risk [38] and similarities in other health-related consequences [39]. This may be important, as an excessive body mass of children was commonly observed in a recent study of Polish adolescents [40]. However, a mother may also transfer her dislikes to her child and create their preferences similar to her own [41].…”
Section: Discussionsupporting
confidence: 84%
“…The association between eating behaviors of mothers and their children that was observed in the conducted study is confirmed by the results of another Polish study, as a similar strong association between eating behaviors of mothers and their adolescent daughters was observed [37], and it also contributed to similar excessive body mass risk [38] and similarities in other health-related consequences [39]. This may be important, as an excessive body mass of children was commonly observed in a recent study of Polish adolescents [40]. However, a mother may also transfer her dislikes to her child and create their preferences similar to her own [41].…”
Section: Discussionsupporting
confidence: 84%
“…The change in the final test was statistically significant, and the percentage of the group of HIIT was 8.8% (moderate ES). The importance of intensity in improving physical aerobic performance was recently confirmed when obese children who did HIIT made remarkably good progress in aerobic capacity development compared to obese children who exercised free activities for six weeks [ 51 ] and after one year long intervention [ 24 ]. Similar results were also found in a recent study from Plavsic and colleagues [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The limitation of the mentioned study was the absence of adolescent girls. In a study with a longer duration (one year) [ 24 ], the extracurricular PA program significantly reduced the BMI, adiposity, and improved body composition of adolescents. A 2 week residential summer camp led to improved body weight, BMI, and self-esteem among obese children (9–14 years) [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of hyperactivity and inattention is challenging, as it is based on own declaration of adolescents, who may want to modify their answers to obtain typical results (as they may be interpreted by adolescent as a better situation). Moreover, the applied intervention, namely LDK program, was associated both with physical activity intervention and nutritional education, which may have contributed to better anthropometric parameters and reduced risk of excessive body mass, as it was observed [35]. However, in such intervention, in spite of the fact that physical activity was the main element, the potential influence of nutritional education may not be neglected.…”
Section: Discussionmentioning
confidence: 99%